Contribution to the Knowledge of the Ore Clasts from the Novo okno Orebody in the Bor Copper Deposit - Drovenik, Matija (Geologija, 1992)
In the Bor copper deposit, Eastern Serbia, the metasomatic and stockwork orebodies are situated in the hydrothermally altered Upper Cretaceous andesites and their pyroclasts. Along the southem border of the altered zone occurs in the fresh Upper Cretaceous andesitic pyroclasts the lenticular orebody Novo okno which includes beside various andesitic clasts also ore clasts ejected by the synchronous volcanic eruption. In the central part of the orebody the ore clasts include predominantly pyrite, rhombic chalcocite and covellite. The central part is surrounded by the ore in which the ore clasts show very often concentric internal structure. They contain in addition to pyrite particularly bornite, as well as chalcopyrite, and at greater distances only chalcopyrite. The author considers that the concentric internal structure of the mentioned clasts originated during the diagenesis, and that both bornite and chalcopyrite are of diagenetic origin.